Årbogen 1: Remains of a tent from the middle mesolithic - Terkelsen, Signe Groot; Oppvang, Janne (Tromura, 2025)
At Årbogen 1, remains of a single tent ring were discovered, consisting of a cleared surface surrounded by stones and a possible flagstone-paved entrance. The finds were concentrated on a cleared surface and primarily consisted of flint. The site is interpreted as a short-term stay by a small group of people. Reliable datings from the tent ring indicate the periods 6644–7025 BC and 7607–8305 BC, with the latter aligning well with the artifact assemblage. The blade material is prominent, and evidence of both pressure flaking/indirect techniques, associated with an eastern tradition, and direct techniques, linked to southern traditions, was observed.
Keywords: Mesolithic; Middle Mesolithic; Tent; Lithic; Blades